Remaining useful life estimation using accelerated degradation test, a gamma process, and the arrhenius model for nuclear power plants - Kang, Minkoo; Lee, Sunjae; Kim, Jong Ho; Yoo, Chan Sei; Jang, Joongsoon; Negatu, Belachew Mekbibe; Park, Sangchul (Journal of Mechanical Science and Technology, 2022)
Predictive maintenance can be performed in nuclear power plants to prevent the failure of their components and equipment. Estimating the remaining useful life (RUL) of the components and equipment is the most important step in a predictive maintenance strategy. In this study, we focus on the RUL estimation of bipolar junction transistors (BJTs). We propose a practical method that applies a gamma process and the Arrhenius model and uses experimental data obtained by performing accelerated degradation tests (ADTs) at high temperatures. Using OriginLab, we chose the most suitable model as the degradation model. We calculated the parameter values of the proposed model using the gamma process and Arrhenius model. We estimated the RULs of BJTs using the proposed method.
Keywords: Accelerated degradation tests; Arrhenius models; Degradation model; Gamma process; Highest temperature; Life estimation; Maintenance strategies; Practical method; Predictive maintenance; Remaining useful lives; Accelerated degradation test; Arrhenius model; Gamma process; Predictive maintenance; Remaining useful life